Promosi Kesehatan Stop Buang Air Besar Sembarangan (BABS) Melalui Pendekatan STBM Pilar Pertama - Nyak Firzah; Susilawati, Susilawati (Yayasan Literasi Sains Indonesia, 2023)
This literature study was conducted to find out the solution to the problem of poor sanitation through the first pillar of Community-Based Total Sanitation (STBM) related to open defecation free (ODF) by using triggering method that works to cause disgust, fear, anxiety, and the sin of open defecation as well as an overview of health promotion to ODF and steps to promote healthy latrines with communal septic tanks as an alternative to ODF. The approach used in this study is literature review analyzing scientific papers, books, and national journals. STBM is an approach to change the hygiene and sanitation behavior through community empowerment using triggering method. The SBS behavior was followed by the use of sanitary facilities in form of healthy latrines. Healthy latrines are an approach with a simple facilitation process that can change bad habits (open defecation) and expect healthy latrines ODF and sanitation obligations in building healthy latrines are part of the community's responsibility. Healthy latrines must be built, owned, and used by the family in a position (inside the house or outside the house) that is easily accessible to the occupants of the house.